Importance of business clinics in Higher Education Institutions - Alvear - Pájaro, Rafael (Universidad Francisco de Paula Santander, 2022)
Business clinics are institutional extension tools that provide care to entrepreneurs, small and medium-sized companies through advice, training and professional attention to the needs of these organizations, which do not have sufficient financial resources to obtain them externally. The implementation of business clinics in higher education institutions greatly benefits the educational community, service users, generating at the same time an increase in local socio-economic development, since the performance of business tasks is promoted thanks to accessibility of the consultancy. One of the main objectives of business clinics is to strengthen the training process of higher-level students, since from practice and experiential learning it is possible to acquire, develop and reinforce the professional skills required in the environment to which they are projected.